(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2013)
Two samplings were performed at low tide, one in December (2009) and the other in January (2010) to determine the microorganisms in the Estero Salado which are indicators of pollution. A total of nine stations were located along the Estero Salado in Sections B, D, E and G. The results obtained in December 2009 indicate a strong bacterial contamination in the water, the values ranged from 180NMP/100 mL to 160000NMP/100 mL total coliforms, fecal coliforms and Escherichia coli, whereas the values for enterococci were 180NMP/100mL to 7900MPN/100 mL for sediment values ranged from 110,000NMP/100g to 360NMP/100 g for total coliforms, fecal coliforms and E. coli and enterococci, values were 300NMP / g to 29000NMP / g, these results are above the maximum permitted levels. Within the physical- chemical parameters affecting pollution were salinity, dissolved oxygen and temperature. In January (2010), total coliforms in water had values between 84NMP/100mL and 7000 NMP/100ml for fecal coliforms (4NMP/100mL - 450NMP/100mL), E coli (1.8 NMP/100mL- 180 NMP/100mL) and enterococci (6NMP/100mL-610NMP/100mL). In sediment values were relatively low in comparison with the data of sediment in December. The data indicate that there are variations in the marked seasons in the Estero Salado, which suppose that there is a continuum of contamination.